Pronunciation Accent of the First Semester TBI Students - Ririn Wilda Artika; Syasi Aulya Harahap; Zia Aliza Zahra; Yani Lubis (Cemara Education and Science, 2025)
Accents significantly influence language comprehension and pronunciation, especially for non-native speakers. This research explores how different accents affect the listening comprehension of English learners and identifies common pronunciation challenges. Drawing on insights from ten academic journals, the study employed surveys and interviews with five participants. Results reveal that unfamiliar accents increase cognitive load, hinder comprehension, and amplify anxiety, particularly when speakers articulate rapidly or use distinct pronunciations. These findings underscore the importance of exposing learners to diverse accents to improve adaptability and global communication skills.